2014
DOI: 10.1080/01488376.2014.896850
|View full text |Cite
|
Sign up to set email alerts
|

Advocacy by Parents of Young Children With Special Needs: Activities, Processes, and Perceived Effectiveness

Abstract: This article examines parental advocacy for young children with disabilities using a subset of data drawn from a larger exploratory and descriptive study on parental advocacy for children with disabilities from birth to age 18 with a sample of 400 participants. Because this article focuses on parents of children from birth to age 6, only parents (n = 76) meeting this criterion were selected. Data were collected through an online survey, with a snowball sample generated through e-mail lists and social media gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 48 publications
4
47
1
Order By: Relevance
“…Consistent with a previous study about parent LA (Wright and Taylor, ), some study participants ( n = 16) reported positive advocacy experiences. These sixteen participants reported that legislators listened to stories about their children; the participants also reported that their meetings with legislators resulted in favourable outcomes.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with a previous study about parent LA (Wright and Taylor, ), some study participants ( n = 16) reported positive advocacy experiences. These sixteen participants reported that legislators listened to stories about their children; the participants also reported that their meetings with legislators resulted in favourable outcomes.…”
Section: Resultssupporting
confidence: 84%
“…Mixed experiences with LA. Unlike previous studies wherein parents only reported positive experiences (Wright and Taylor, 2014), in this study, parents reported mixed experiences with respect to LA. Parents who reported positive experiences reported that their legislators listened to their stories resulting in policy changes.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…The authors noted "since the outset of the austerity programme, platforms such as blogs, Twitter and Facebook have proved important tools for disability activism in challenging government policy" (p. 928). Wright and Taylor (2014) gave a questionnaire through social media to parents of children with special needs. Of the 76 participants with children from birth to age 6, 51% indicated social media as a place for advocacy and 13% indicated social media was a "highly effective" (p. 597) way to advocate.…”
Section: "Whilst Dpac's Approach To Online Media Prior To Thementioning
confidence: 99%
“…According the Council of Parent Attorneys and Advocates (COPAA), which focuses on special education advocacy, an advocate is defined as, “…someone who speaks, writes in favor of, supports, advises or urges by argument in support of another person,” (COPAA, 2012b). In the parent advocacy literature, however, the term “advocate” has been described differently in a variety of contexts (Wright & Taylor, 2014), approaches (Trainor, 2010), and activities (Balcazar, Keys, Bertram, & Rizzo, 1996). To fulfill the post-graduation requirement of the VAP training, graduates may engage in a broadly defined range of advocacy activities related to the special education needs of the child, with the goal of working towards provision of FAPE for students with disabilities (COPAA, 2008).…”
mentioning
confidence: 99%